2015
DOI: 10.1177/0004867415607984
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based stress reduction for long-term physical conditions: A systematic review

Abstract: Although there is some preliminary support for the use of mindfulness-based stress reduction in physical health conditions, further research is required before it could be considered an effective intervention for improving physical health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 55 publications
(93 reference statements)
4
35
0
3
Order By: Relevance
“…In the treatment of long-term medical conditions, mindfulness-based therapies (excluding MBCT) have some evidence [11]. Applications of mindfulness to tinnitus are in their infancy, and as yet there have been just 7 relevant studies published, of which only 2 are randomized controlled trials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of long-term medical conditions, mindfulness-based therapies (excluding MBCT) have some evidence [11]. Applications of mindfulness to tinnitus are in their infancy, and as yet there have been just 7 relevant studies published, of which only 2 are randomized controlled trials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…25, 27 Clinical trials in adults have shown that various forms of mindfulness meditation result in improvement in pain, physical function, anxiety, and depression. 2832 There are also data that support the use of MBSR in children and adolescents both for reducing perceived stress and for improving psychological health. 33 In this pilot study, we assessed the feasibility of an MBSR program for adolescents with widespread chronic pain and other persistent somatic symptoms, and to make preliminary assessments of its clinical utility.…”
mentioning
confidence: 99%
“…Both studies were approved by University of Otago Human Ethics Committee (Feasibility—H13/102 & Pilot—H15/003). In parallel with the preliminary studies, we undertook two literature reviews (Crowe et al., , ). Our review on Mindfulness‐based Stress Reduction (MBSR) aimed to identify whether the MBSR modality improved physical health for people with LTCs (Crowe et al., ).…”
Section: Step 1: Needs Assessment Data From Two Preliminary Studies mentioning
confidence: 99%
“…In parallel with the preliminary studies, we undertook two literature reviews (Crowe et al., , ). Our review on Mindfulness‐based Stress Reduction (MBSR) aimed to identify whether the MBSR modality improved physical health for people with LTCs (Crowe et al., ). A second review on transdiagnostic health management interventions was conducted to assess their clinical effectiveness for older people with multimorbidity (Crowe et al., ).…”
Section: Step 1: Needs Assessment Data From Two Preliminary Studies mentioning
confidence: 99%